THE USE OF SOCIAL MEDIA TO LEARN ENGLISH FOR UNIVERSITY STUDENTS - Nama, Darius Yonatan (ELite Journal : International Journal of Education, Language and Literature, 2024)
This study aimed to investigate the perceptions, potential benefits, and challenges associated with the utilization of social media in English language learning, with a particular focus on English education students. 20 students participated voluntarily. This research applied a mixed-method research design by utilizing a questionnaire and interview. Positive aspects, such as real-life practice and connections with native speakers, coexist with divergent views on engagement, convenience, and cost-effectiveness. The mixed perception regarding its impact on motivation emphasizes the intricate nature of this educational medium. Identified challenges, encompassing distractions and language barriers, highlight the multifaceted nature of the experience. Positive perceptions, including maintaining focus and effective time management, provide a comprehensive understanding of learning English on social media. The diversity in perspectives underscores the need for a tailored approach to leveraging social media benefits for language education. Students' suggestions offer valuable strategies for mitigating challenges, ranging from improved data accessibility to a deliberate focus on educational content. Individualized recommendations, such as adaptive learning approaches and goal setting, provide practical avenues for educators and learners. The article emphasizes the importance of crafting educational strategies with a nuanced understanding of students' perceptions, contributing to the continual refinement of language education in contemporary digital landscapes.